2011
DOI: 10.5858/2010-0018-rs.1
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohyponatremia Revisited: A Modern-Day Pitfall

Abstract: Factitiously low sodium estimations are a hazard in most modern clinical laboratories. Most modern high-throughput analyzers use indirect ion-selective electrodes to estimate electrolyte concentrations in serum samples. This analysis is preceded by a dilution step of the sample. If the water concentration is altered by the presence of increased lipid or protein, the dilution step and the subsequent calculation of concentration by the analyzer results in a falsely low sodium value. This places patients at risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…But in current clinical practice, most of the laboratories use indirect potentiometry using an ion-selective electrode that has a sodium selective membrane, which measures the potential generated across a sodium selective membrane, when immersed in a serum sample [ 5 , 11 ]. The potential generated is a function of the activity of sodium ions in the sample [ 5 , 7 , 11 ]. The activity of an element is described as a measure of the number of atoms that act completely as ions per unit volume of electrolyte solution [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But in current clinical practice, most of the laboratories use indirect potentiometry using an ion-selective electrode that has a sodium selective membrane, which measures the potential generated across a sodium selective membrane, when immersed in a serum sample [ 5 , 11 ]. The potential generated is a function of the activity of sodium ions in the sample [ 5 , 7 , 11 ]. The activity of an element is described as a measure of the number of atoms that act completely as ions per unit volume of electrolyte solution [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pseudohyponatremia, the water component is diluted by non-aqueous materials such as lipids and proteins. In conditions like hyperlipidemia and hyperproteinemia, abnormally high levels of these large molecules replace the aqueous phase of plasma, thus resulting in a reduced amount of serum electrolytes per unit volume of serum [ 6 , 7 ]. When measured with conventional flame photometry or indirect potentiometry, which involves prior dilution of the samples, the measured sodium concentration is low but the true plasma concentration is normal [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So pseudohyponatremia or pseudonormonatremia should be ruled out. [10][11][12] So, there is an advantage with direct ISE method because results are unaffected by the presence of abnormal protein and lipid content, whereas indirect ISE results get affected. 13,14 Chow et al showed that hypoproteinemia may lead to reporting of falsely high Na + values by indirect ISE method.…”
Section: Discussionmentioning
confidence: 99%
“…It involves direct potentiometry and is used in point-of-care blood gas analyzers. The second method is indirect ISE, which is used in routine chemistry analyses in central laboratories, and it includes a pre-analysis serum or plasma dilution step [8,9].…”
Section: Discussionmentioning
confidence: 99%